Understanding perceptions of emotional eating among Thai upper secondary school students: a descriptive qualitative study - Sarnkhaowkhom, Chawapon; Glangkarn , Sumattana; Bourneow , Chaiwut; Suwathanpornkul , Ittipaat (Universitas Airlangga, 2026)
Introduction: Emotional eating has been recognized as a contributing factor to both being overweight and developing obesity, which are associated with increased risk of non-communicable diseases (NCDs), particularly among adolescents. Psychological and environmental stressors have exacerbated concerns regarding emotional eating by disrupting daily routines and influencing eating behaviors worldwide. This study sought to investigate the viewpoints and perspectives, underlying motivations, and personal experiences related to emotional eating among upper secondary school students in Thailand. Methods: A descriptive qualitative approach was used to obtain a comprehensive insight into this phenomenon. Twelve Thai upper secondary school students who met the inclusion criteria participated in in-depth interviews. The interviews were recorded, transcribed word for word or verbatim, and examined through content analysis based on the framework proposed by Vears and Gillam. Results: The analysis revealed five main themes and 15 subthemes: (1) perceived meaning of emotional eating, (2) behavioral characteristics of emotional eating, (3) motivational drivers of emotional eating, (4) perceived consequences of emotional eating, and (5) self-management when experiencing emotional eating. The findings highlight that emotional eating in students is shaped by complex interactions between emotional states, internal psychological factors, and social influences. Conclusions: This study describes how Thai upper secondary school students understand and manage emotional eating, underscoring the importance of addressing emotional and behavioral health in nutritional interventions. Further research should focus on developing contextually appropriate strategies to support healthy eating habits and emotional resilience in adolescence. This is a critical period in physical and psychological development.